Effects of Cichorium glandulosum on hyperglycemia, dyslipidemia and intestinal flora in db/db mice. (October 2022) - Yan, Junlin; Kang, Jinsen; Chen, Bingting; Zhong, Yewei; Abudurexiti, Adalaiti; Zhang, Rui; Tan, Huiwen; Ma, Xiaoli
Graphical abstract: Highlights: Study on the hypoglycemic and lipid-lowering effects of Chicory on db/db mice. Effect of Chicory on db/db intestinal flora. Relationship between intestinal flora and insulin resistance, short chain fatty acids. Abstract: This study aimed to investigate the effects of Cichorum glandulosum Boiss. et Huet. whole herb extract (CG) on hypoglycemic, lipidemic effects, and intestinal flora in db/db mice. The experimental results showed that CG orally administered to db/db mice had specific hypoglycemic activity. CG could effectively alleviate the lipid accumulation in liver tissues, improve the antioxidant capacity and thus liver injury in db/db mice. In addition, CG treatment can activate uncoupling protein ( UCP-1 ) and improve the dysbiosis in the intestine. These findings suggest that CG has particular hypoglycemic activity, can improve blood lipid and intestinal flora disorders in db/db mice, reduce Firmicutes/Bacteroide, by affecting the gut-fat axis, promote the process of white fat browning in db/db mice, thus reducing insulin resistance in the body, and can be used for the prevention and treatment of type 2 diabetes.